Iraq : First Review of the Three-Year Stand-By Arrangement and Financing Assurances Review, Requests for Waivers of Nonobservance and Applicability of Performance Criteria, Modification of Performance Criteria, and Rephasing of the Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Iraq's First Review of the Three-Year Stand-by Arrangement (SBA) and Financing Assurances Review, and Requests for Waivers of Nonobservance and Applicability of Performance Criteria (PCs). Two PCs at end September appear to have been met on the basis of preliminary unaudited data. One PC at end-June 2016 was missed. One continuous PC was missed. Completion of some structural benchmarks was delayed, but progress is being made for each. Hence, program performance has been mixed, but understandings on sufficient corrective actions have been reached to put the program back on track. The IMF staff recommends completion of the first review under the SBA and the financing assurances review and modification of the PCs and related rephrasing.